A modern introduction to differential equations - Ricardo, Henry J. ([Place of publication not identifed] : [publisher not identified], 2009)
"A Modern Introduction to Differential Equations presents a solid yet highly accessible introduction to differential equations, developing the concepts from a dynamical systems perspective and employing technology to treat topics graphically, numerically and analytically. This text is designed to be appropriate for a wide variety of students and exists as a natural successor to any modern calculus sequence."--Publisher's website.
Ch. 1. Introduction to Differential Equations -- Ch. 2. First-Order Differential Equations -- Ch. 3. Numerical Approximation of Solutions -- Ch. 4. Second- and Higher-Order Equations -- Ch. 5. Systems of Linear Differential Equations -- Ch. 6. Laplace Transform -- Ch. 7. Systems of Nonlinear Differential Equations -- Appendix A. Some Calculus Concepts and Results -- Appendix B. Vectors and Matrices -- Appendix C. Complex Numbers -- Appendix D. Series Solutions of Differential Equations -- Answers/Hints to Odd-Numbered Exercises.
Includes bibliographical references and index.
Keywords: DIFFERENTIAL EQUATIONS